2020
DOI: 10.1016/s1474-4422(19)30487-9
|View full text |Cite
|
Sign up to set email alerts
|

Feast or famine in multiple sclerosis therapeutics

Abstract: See Articles page 214 Fanatic Studio/Science Photo Library I declare personal consulting fees from Actelion, Biogen, Celgene, EMD Serono, Genentech, Immunic, Novartis, Sanofi, Teva, and TG Therapeutics; have served on clinical trial advisory committees for Actelion, Biogen, Immunic, and Novartis; and have received clinical trial contract and research grant funding from Biogen and Novartis. I thank Jeffrey Cohen (Cleveland Clinic) for critical review of this Comment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…1 In contrast, a sensitive and specific biomarker for use in progressive MS remains to be established. 2…”
Section: Introductionmentioning
confidence: 99%
“…1 In contrast, a sensitive and specific biomarker for use in progressive MS remains to be established. 2…”
Section: Introductionmentioning
confidence: 99%
“…Finally, some have suggested that the literature-based systematic review approach to drug selection is intrinsically flawed because it does not take into account disease specific pathophysiology (which may be largely unknown). 47 While the three drugs tested in MS-SMART were not effective, 18 we note that two other drugs on the final MS-SMART shortlist -ibudilast 20 and lipoic acid 21 have since shown promise in independent phase II trials. Lipoic acid has been identified again as a favourable candidate drug in a further, independent review in 2020.…”
Section: Open Accessmentioning
confidence: 90%
“…Finally, some have claimed that the literature-based systematic review approach to drug selection is intrinsically flawed because it does not take into account disease specific pathophysiology (which may be largely unknown). [39] While the three drugs tested in MS-SMART were not effective, [15] we note that two other drugs on the final MS-SMART shortlist -ibudilast [17] and lipoic acid [18] -have since shown promise in independent phase II trials. Lipoic acid has been identified again as a favourable candidate drug in a further, independent review in 2020.…”
Section: Limitations Of This Approachmentioning
confidence: 99%